(Invited) Capabilities of Analytical Transmission Electron Microscopy for the Analysis of Structural, Chemical and Electronic Properties Exemplified by the Study of Y-Doped (Ba, Sr)(Co, Fe)O3-δ. (13th April 2015) - Meffert, Matthias; Störmer, Heike; Gerthsen, Dagmar
Abstract : The effect of Y-doping on secondary phase formation was studied in (Ba0.5 Sr0.5 )(Co0.8 Fe0.2 )O3-δ to avoid degradation of the oxygen permeation in this material. B-site cations were substituted by up to 10 % Yttrium. The microstructure was studied by analytical transmission electron microscopy. This also includes the investigation of A- and B-site occupation by Y-cations using atom location by channeling enhanced microanalysis (ALCHEMI).